The effect of gender-based violence on the realisation of the right to health for women in Kenya - Killander, Magnus (University of Pretoria, 2025)
Mini Dissertation (LLM (Human Rights Specialising in Sexual and Reproductive Rights in Africa))--University of Pretoria, 2025.